State Ownership and Risk-Taking Behaviour: Evidence from Malaysia's Banking Industry - Lee, Ai-Xin; Chee, Wooi Hooy (UUM Press, 2020)
This study investigates state ownership on risk-taking behaviour in Malaysias banking industry. Using the panel of Malaysian commercial banks, this paper examines whether banks risk-taking is affected by Malaysian government ownership through the five largest investment arms of Malaysia (GLICs). The findings show that state-owned banks exhibit higher risk-taking behaviour compared to the private-owned banks in terms of loans. There is evidence that a higher degree of state ownership has a more significant impact on banks risk-taking behaviour. We also investigate the relationship with corporate governance mechanisms. The findings suggest that the composition of board of directors somehow plays a significant role in the governance of banks.